Legume-based green concentrate alleviates negative energy balance and enhances performance, metabolic health, and profitability in postpartum Holstein Friesian cows - Renny Fatmyah Utamy; Ambo Ako; Zyahrul Ramadan; Yasuyuki Ishii; Mohammad Mijanur Rahman; Kannika Umpuch; Azisah Nurfadilah; Gemal Umar Akmal Alkatiry; Muhammad Akram; Jiant Muthahra Maharani (Veterinary World)
Background and Aim: Negative energy balance (NEB) is a common metabolic disorder in postpartum dairy cows that compromises milk yield, metabolic health, and reproductive function. Sustainable nutritional interventions are essential to mitigate NEB without increasing production costs. This study evaluated the effect of a legume-based green concentrate (GC) containing Gliricidia sepium and Indigofera zollingeriana on performance, hormonal profiles, and beta-hydroxybutyrate (BHB) levels in Holstein Friesian (HF) cows experiencing NEB.